2020
DOI: 10.1101/2020.11.26.400416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revisiting the Neural Architecture of Adolescent Decision-Making: Univariate and Multivariate Evidence for System-Based Models

Abstract: System-based theories are a popular approach to explaining the psychology of human decision making. Such theories posit that decision-making is governed by interactions between different psychological processes that arbitrate amongst each other for control over behavior. To date, system-based theories have received inconsistent support at the neural level, leading some to question their veracity. Here we examine the possibility that prior attempts to evaluate system-based theories have been limited by their re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 95 publications
(192 reference statements)
0
2
0
Order By: Relevance
“…Contradictory to the neurodevelopmental imbalance models, a meta-study exploring the age difference did not observe risk-taking differences between early adolescents (11-13 years) and children (5-10 years). A recent study further challenged this model, showing that multivariate brain activity metrics of dlPFC can predict adolescent risk decision tendencies (Moreira et al, 2021).…”
Section: The Conjunction and Contrast Results Of The Age Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Contradictory to the neurodevelopmental imbalance models, a meta-study exploring the age difference did not observe risk-taking differences between early adolescents (11-13 years) and children (5-10 years). A recent study further challenged this model, showing that multivariate brain activity metrics of dlPFC can predict adolescent risk decision tendencies (Moreira et al, 2021).…”
Section: The Conjunction and Contrast Results Of The Age Differencementioning
confidence: 99%
“…Contradictory to the neurodevelopmental imbalance models, a meta‐study exploring the age difference did not observe risk‐taking differences between early adolescents (11–13 years) and children (5–10 years). A recent study further challenged this model, showing that multivariate brain activity metrics of dlPFC can predict adolescent risk decision tendencies (Moreira et al, 2021 ). Unlike the neurodevelopment imbalance models, these results demonstrated that adolescent dlPFC did not crucially have fewer effects on risk‐taking behavior than their reward systems.…”
Section: Discussionmentioning
confidence: 99%